Farming schemes and characteristics of Kalibening Avocado in Kebondalem Village, Semarang Regency, Central Java. Issue 2 (July 2021) - Tan, S S; Indrasti, R; Handoko, S; Malik, A; Cempaka, I G
Abstract: One of the plants that have high economic prospects is the avocado plant. In addition to its various benefits, from fruit to leaves, avocado also has a high economic value and has the potential to be developed in Indonesia. One of the avocados that have good prospects is the Kalibening avocado in Kalibening Hamlet, Kebondalem Village, Jambu District, Semarang Regency, Central Java. This study aims to determine the characteristics and income level of Kalibening avocado farmers which is carried out using two farming schemes, seedling nursery scheme and avocado fruit farming scheme. The results of the study can be used for the development of avocado plants in other areas in Indonesia to meet market demand for avocados. This study uses a survey method, namely taking samples or respondents from a population using a questionnaire as a data collection tool. Observations of plant characters and the results of Kalibening Avocado descriptions were analyzed qualitatively and tabulated according to predetermined parameters, then presented in tabular form. The results of the study show that one of Kalibening avocado characters is its capability to grow and develop very well in various topographies, either in the highlands or in the lowlands. Furthermore, the results of farming analysis show that the sales of seeds and fruit are profitable so that they are feasible to be developed in various regions in Indonesia.